Maternal outcome of grand multipara - Shahida, SM; Islam, MA; Begum, S; Hossain, MA; Azam, MS (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):381-385 The abstract of this article is available on the PubMed website